2016
DOI: 10.1371/journal.pone.0148858
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Anti-Arrhythmic Effects of Heptanol in Langendorff-Perfused Mouse Hearts

Abstract: Acute effects of heptanol (0.1 to 2 mM) on atrial electrophysiology were explored in Langendorff-perfused mouse hearts. Left atrial bipolar electrogram or monophasic action potential recordings were obtained during right atrial stimulation. Regular pacing at 8 Hz elicited atrial activity in 11 out of 11 hearts without inducing atrial arrhythmias. Programmed electrical stimulation using a S1S2 protocol provoked atrial tachy-arrhythmias in 9 of 17 hearts. In the initially arrhythmic group, 2 mM heptanol exerted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Previous studies in mouse models have associated increased arrhythmogenicity with reduced CVs, prolonged or shortened APDs and reduce ERPs (2,3,5,7,12). These values were therefore obtained from the experimental recordings described above.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies in mouse models have associated increased arrhythmogenicity with reduced CVs, prolonged or shortened APDs and reduce ERPs (2,3,5,7,12). These values were therefore obtained from the experimental recordings described above.…”
Section: Resultsmentioning
confidence: 97%
“…The right ventricular epicardium was electrically stimulated using either regular 8 Hz or S1S2 pacing (2,3,5,7,12). MAP recordings were obtained from the left ventricular epicardium.…”
Section: Resultsmentioning
confidence: 99%
“…Besides voltage sensitivity, both mechanosensitivity and chemosensitivity have been reported (Bao et al, 2004; Bukauskas and Verselis, 2004). Connexin activity is influenced by intracellular Ca 2+ , pH, chemical uncouplers (Tse et al, 2016b,c,d,e,f), phosphorylation events (Musil and Goodenough, 1991; Bennett and Verselis, 1992), and lipid availability in the immediate environment, including low-density lipoprotein, apolipoprotein-B (Meyer et al, 1991) and cholesterol (Meyer et al, 1990). Gap junctions allow the passive diffusion of ions, intracellular molecules that include metabolites and messengers such as cyclic AMP, cyclic GMP and IP 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, optical mapping using a microelectrode array would be a better technique [50]. Furthermore, the MAP electrode would cover the entire mouse atrial surface for studying atrial electrophysiological properties, but MAPs have been successfully recorded from the mouse atria [51]. Other methods such as bipolar electrograms can also be used to determine repolarization properties [51,52].…”
Section: Practical Considerations and Limitationsmentioning
confidence: 99%
“…It is unclear as to the minimum degree of intercellular coupling needed for obtaining MAP recordings and the effects of impaired gap junction function on the MAP waveform. Experimental studies in mouse hearts have demonstrated stable MAP recordings obtained from myocardium when gap junctions were uncoupled by the agent heptanol at a concentration of 0.1 mM [20,35,51]. At a higher concentration of 2 mM, conduction velocity was progressively reduced and MAP amplitudes were decreased, eventually leading to conduction block and abolition of the MAP waveform.…”
Section: Practical Considerations and Limitationsmentioning
confidence: 99%